2019
DOI: 10.1021/acs.orglett.9b00419
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of (−)-Oxycodone via Anodic Aryl–Aryl Coupling

Abstract: A fully regio- and diastereoselective electrochemical 4a–2′-coupling of a 3′,4′,5′-trioxygenated laudanosine derivative enables the synthesis of the corresponding morphinandienone. This key intermediate is further transformed into (−)-oxycodone through conjugate nucleophilic substitution for E-ring closure and [4 + 2] cycloaddition with photogenerated singlet oxygen to accomplish diastereoselective hydroxylation at C-14. The anodic transformation provides high yields and can be performed under constant current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 81 publications
1
63
0
Order By: Relevance
“…Early studies by the Waldvogel laboratory have demonstrated that phenols can be electro‐oxidatively coupled to produce biphenols as well as polycyclic scaffolds . A related strategy was recently employed by the Opatz and Waldvogel groups in the syntheses of (−)‐thebaine and (−)‐oxycodone . Here, regio‐ and diastereoselective intramolecular anodic coupling of laudanosine derivatives afforded the corresponding morphinandienone motifs, which were further elaborated to the desired target structures (Schemes and ).…”
Section: Anodic Oxidationmentioning
confidence: 99%
“…Early studies by the Waldvogel laboratory have demonstrated that phenols can be electro‐oxidatively coupled to produce biphenols as well as polycyclic scaffolds . A related strategy was recently employed by the Opatz and Waldvogel groups in the syntheses of (−)‐thebaine and (−)‐oxycodone . Here, regio‐ and diastereoselective intramolecular anodic coupling of laudanosine derivatives afforded the corresponding morphinandienone motifs, which were further elaborated to the desired target structures (Schemes and ).…”
Section: Anodic Oxidationmentioning
confidence: 99%
“…In 2019, Opatz and co-workers reported one of the most efficient and elegant total syntheses of (-)-oxycodone, using as key steps an electrochemical cyclization and an endoperoxidation photocatalyzed by TPP in an almost gram-scale (Scheme 38) [88].…”
Section: Singlet Oxygen In Pericyclic Reactionsmentioning
confidence: 99%
“…Later, this general route was combined with anodic C−C aryl coupling to provide a biomimetic access to the natural product (−)‐thebaine ( 137 ) and the semisynthetic opioid (−)‐oxycodone (see Scheme ) . As starting materials for these syntheses, bromides 126 and 125 were prepared from methyl gallate 123 .…”
Section: α‐Aminonitriles As Key Intermediates In Natural Product Syntmentioning
confidence: 99%